ANLISIS KASUS UPAH LEMBUR DI PT SAI APPAREL INDUSTRIES: TINJAUAN PELANGGARAN DAN HAK PEKERJA - Nurwahid, Muhammad Humam Hikmah; Fatriani, Fenny (LPPM Universitas Bina Bangsa, 2025)
The issue of paying overtime wages is an important issue in Indonesian employment that is often ignored by companies, including in the case of PT SAI Apparel Industries. This article analyzes alleged violations of overtime pay committed by companies against their employees using a juridical and normative approach. Based on statutory regulations, in particular Article 78 paragraph (2) and Article 85 of the Manpower Law and PP Number 35 of 2021, companies are obliged to pay overtime wages in accordance with applicable regulations. However, it was found that PT SAI Apparel Industries did not record overtime hours properly and did not pay compensation in full, violating workers' rights to a living wage. These violations not only impact workers' welfare but also cause dissatisfaction and have the potential to lead to industrial conflicts. To resolve this case, steps such as mediation through the Manpower Service, filing a lawsuit with the Industrial Relations Court, and strict supervision by the government are proposed as solutions. In addition, companies need to increase transparency in working time management and ensure compliance with regulations. Enforcing workers' rights to overtime pay is a crucial step in building harmonious industrial relations and creating justice for both parties.